2013
DOI: 10.1002/pop4.36
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Housing Choice Voucher Households on Neighborhood Crime: Longitudinal Evidence From Dallas

Abstract: Tenant-based housing assistance is designed to provide access for low-income households to a wider range of housing options, de-concentrating poverty and reducing the exposure of these households to negative conditions. Yet an observed coincidence of crime and subsidized households indicates that something is going wrong. Either households are constrained in their choices and are settling in high-crime neighborhoods, or these households bring crime with them, using vouchers to penetrate otherwise low-crime nei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
11
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 23 publications
2
11
0
Order By: Relevance
“…They found that homicides moved to the parts of the city where public housing and voucher tenants moved, although their analyses were cross-sectional rather than longitudinal. Van Zandt and Mhatre (2009) examined the relationship between clusters of housing voucher households and crime in Dallas, TX. They considered a cluster to be 10 or more voucher households during any month between October 2003 and July 2006, and examined crime data within a quarter-mile radius of the apartment complexes containing these voucher clusters.…”
Section: Empirical Evidencementioning
confidence: 99%
“…They found that homicides moved to the parts of the city where public housing and voucher tenants moved, although their analyses were cross-sectional rather than longitudinal. Van Zandt and Mhatre (2009) examined the relationship between clusters of housing voucher households and crime in Dallas, TX. They considered a cluster to be 10 or more voucher households during any month between October 2003 and July 2006, and examined crime data within a quarter-mile radius of the apartment complexes containing these voucher clusters.…”
Section: Empirical Evidencementioning
confidence: 99%
“…One unpublished paper specifically analyzes the effect of voucher locations on surrounding crime rates. Van Zandt and Mhatre (2009) analyze crime data within a quarter mile radius of apartment complexes containing 10 or more voucher households during any month between October 2003 and July 2006 in Dallas. Unfortunately, the police did not collect crime data in these areas if the number of voucher households dipped below 10, leading to gaps in coverage and limiting the number and type of neighborhoods examined.…”
mentioning
confidence: 99%
“…While this study focused specifically on transportation affordability, there are potential tradeoffs of location efficiency characteristics and other qualities of the area. Some possible tradeoffs mentioned in affordable housing literature are school quality [42], congestion [43], neighborhood crime [44], pollution or environmental quality [43], poverty concentration and racial segregation [45]. Our study did not capture such tradeoffs due to data limitations at the national level, but again the focus of this study was not on the residential choice of low-income households, rather to measure the effectiveness of HUD programs in terms of transportation affordability.…”
Section: Discussionmentioning
confidence: 99%